Opioid System and Epithelial–Mesenchymal Transition - Marzena Łazarczyk; Dominik Skiba; Michel-Edwar Mickael; Kinga Jaskuła; Agata Nawrocka; Piotr Religa; Mariusz Sacharczuk (Pharmaceuticals)
Opioids are a challenging class of drugs due to their dual role. They alleviate pain, but also pose a risk of dependency, or trigger constipation, particularly in cancer patients, who require the more potent painkillers in more advanced stages of the disease, closely linked to pain resulting from general inflammation, bone metastases, and primary or secondary tumour outgrowth-related nerve damage. Clinicians’ vigilance considering treatment with opioids is necessary, bearing in mind extensive data accumulated over decades that have reported the contribution of opioids to immunosuppression, tumour progression, or impaired tissue regeneration, either following opioid use during surgical tumour resection and post-surgical pain treatment, or as a result of other diseases like diabetes, where chronic wounds healing constitutes a challenge. During last few years, an increasing trend for seeking relationships between opioids and epithelial–mesenchymal transition (EMT) in cancer research can be observed. Transiently lasting EMT is desirable during wound healing, but in cancer, or vital organ fibrogenesis, EMT appears to be an obstacle to overcome, forcing to adjust treatment strategies that would reduce the risk for worsening of the disease outcome and patient prognosis. The same opioid may demonstrate promoting or inhibitory effect on EMT, dependently on various conditions in particular clinical cases. We have summarized current findings on this issue to uncover some rules that govern opioid-mediated EMT induction or repression; however, many aspects still remain to be elucidated.